Energy efficiency in public educational institutions in Brazil: a bibliographical study - Firmino, Emily Haley Gomes; Alves, Ingrid Heloisa da Silva (Brazilian Journal of Production Engineering, 2024)
Energy efficiency consists of the rational use of energy and is directly related to sustainable development. Educational institutions are centers responsible for transmitting scientific knowledge and information, and thus can provide practical examples of sustainability to the internal and external community. This work aims to verify how the topic of energy efficiency has been treated and applied in educational institutions and what impacts this discussion has caused on the institution itself, its users and society. To this end, a survey of scientific articles published in journals since 2023 was carried out, which present examples of analysis, implementation and awareness approaches, in addition to possible improvements suggested and applied to contribute to efficiency in educational institutions of energy and to the debate on sustainability. We will be able to understand the different approaches used to discuss energy efficiency, some participating in teaching, others in research and others in extension or practical application. The dissemination of information on energy efficiency in this environment contributes to a participatory learning environment, promotes the stimulation of teaching on environmental education, in addition to encouraging users of the facilities to adopt sustainable practices, such as the rational use of energy.